A Constant Exponent Coefficient Fixed-Time Control For Voltage Regulating DC-DC Converter - Cholahan, Varin; Wongvanich, Napasool; Tangsrirat, Worapong (My University, 2025)
This research examines the voltage regulation capabilities of a DC-DC converter that employs the Fixed-Time control (FTSMC) method, incorporating a Constant Exponent Coefficient reaching law technique. The suggested approach is characterized by its simplicity, stability, and robustness, especially in the face of significant variations in load demands and input voltage. A state-space average dynamical model (SSA) is formulated. Initially, Continuous Conduction Mode (CCM) is established, followed by the development of the more advanced Discontinuous Conduction Mode (DCM). The nonlinear model considers two variables associated with the controlled voltage and the inductor coil current as state variables. To estimate unknown parameters, the feedback linearization method is applied. The dynamic system's output voltage is regulated using a Fixed-Time control technique. The proposed control system's stability is validated through the application of Lyapunov's theorem, which guarantees closed-loop stability. Finally, the simulation outcomes indicate the performance regulation relative to conventional linear controllers.
Keywords: DC-DC Converter; Fixed-Time control; Nonlinear Control; Sliding Mode Control